Do We Need to Change the Outlook? - Kishore, Surekha (Indian Journal of Community Health, 2018)
Family Medicine is a complex branch by virtue of its nature. Broad in its perspective, it involves high proportion of poorly differentiated problems along with overlapping biological, psychological, and social factors.(1) EBM (Evidence Based Medicine) which originated in second half of 19th century, roused greater interest among health professionals especially during last decade (1). With time as medical knowledge grew, EBM was internationally accepted as gold standard for decision-making and standard for medical practice. It facilitated clinicians in providing up-to-date scientific evidence which in combination with clinical expertise was utilized in medical practice to achieve best possible outcomes (2). Evidence-based practice guidelines and EBM approaches are recognized as the core of today’s scientific thinking with randomized controlled trials (RCTs) being regarded as fundamental research response of EBM for healthcare (3). However, the most troubling aspect of EBM is that it provides the restricted view of evidence. As advocated since 1990s, it was based on the notion that medical practice was subjective and evidence should rather be prioritized on hierarchical system. To promote greater reliance on published literature, RCTs were introduced as a powerful tool for measuring effectiveness and safety of treatments. It argued that clinical judgment and mechanistic reasoning are less reliable forms of evidence in medicine (4,5). Despite EBM era, they still continues to exert influence, resulting in confusion and controversy.